Community Dependency and Vulnerability to Natural Resources: Case Study Mount Geulis University Forest - Muhammad Rizky Darmawan; Ichsan Suwandhi; Mulyaningrum Mulyaningrum (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
Mount Geulis University Forest (MGUF) is a university forest area surrounded by eight villages and has close relationships with the surrounding community. With a very strategic position, MGUF is vulnerable to various pressures, especially anthropogenic ones. Other studies have shown that population, development, and the economy have an essential role in environmental degradation. Thus, understanding these three things becomes essential to determine the right strategy to reduce the level of vulnerability around MGUF. This study aims to analyze the level of community dependency on MGUF and the level of vulnerability of the community around MGUF. Community dependency was analyzed using perceived value dependency on livelihood, perceived value dependency on income, and perceived value dependency on participation level. Community vulnerability was analyzed based on the population growth index, built-up land index, and economic openness index. The results showed that the farmer community had a relatively high dependency on MGUF. The lower the income, the higher the dependency on MGUF, and the participation rate increases as the dependency on MGUF increases. Raharja Village has the highest population growth index of 123.75, Mangunarga Village has the highest built-up land index with a value of 75.11, and Jatimukti Village has the highest economic openness index with a value of 33.52. In general, the village with the highest composite vulnerability index is Cikahuripan Village, with a value of 0.71, and the lowest is Jatiroke, with a value of 0.20. Based on the value of the vulnerability index and the level of security, the level of vulnerability can be reduced by carrying out collaborative management to run programs with every stakeholder in the MGUF management system.